Amniotic fluid allograft enhances the host response to ventral hernia repair using acellular dermal matrix. (11th October 2021) - Van Eps, Jeffrey L.; Boada, Christian; Scherba, Jacob C.; Zavlin, Dmitry; Arrighetti, Noemi; Shi, Aaron; Wang, Xin; Tasciotti, Ennio; Buell, Joseph F.; Ellsworth, Warren A.; Bonville, Daniel J.; Fernandez‐Moure, Joseph S.
Abstract: Ventral hernia repair (VHR) with acellular dermal matrix (ADM) has high rates of recurrence that may be improved with allogeneic growth factor augmentation such as amniotic fluid allograft (AFA). We hypothesized that AFA would modulate the host response to improve ADM incorporation in VHR. Lewis rats underwent chronic VHR with porcine ADM alone or with AFA augmentation. Tissue harvested at 3, 14, or 28 days was assessed for region‐specific cellularity, and a validated histomorphometric score was generated for tissue incorporation. Expression of pro‐inflammatory ( Nos1, Tnfα ), anti‐inflammatory ( Arg1, Il‐10, Mrc1 ) and tissue regeneration ( Col1a1, Col3a1, Vegf, and alpha actinin‐2 ) genes were quantified using quantitative reverse‐transcription polymerase chain reaction. Amniotic fluid allograft treatment caused enhanced vascularization and cellularization translating to increased histomorphometric scores at 14 days, likely mediated by upregulation of pro‐regeneration genes throughout the study period and molecular evidence of anti‐inflammatory, M2‐polarized macrophage phenotype. Collectively, this suggests AFA may have a therapeutic role as a VHR adjunct.